A tin-based perovskite thin film, a preparation method thereof and a solar cell
By introducing terephthalic acid cations into tin-based perovskite films to form a network envelope structure, the stability and coverage issues of tin-based perovskite films were solved, thus improving the performance of solar cells.
Patent Information
- Application Number
- CN202210284173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-03-22
AI Technical Summary
Tin-based perovskite films suffer from poor stability and low coverage, leading to direct contact between the electron transport layer and the hole transport layer, which in turn causes device failure.
A perovskite structure with the chemical composition RAn-1BnX3n+1, where R is a divalent terephthalic acid cation, A is a monovalent organic cation, B is a divalent tin ion, and X is a halide ion, is used to prepare tin-based perovskite films by spin coating and annealing. The network envelope structure formed by terephthalic acid cation, organic ammonium salt, and tin salt inhibits ion migration and slows down the crystallization rate.
This improved the stability and substrate coverage of tin-based perovskite films, thereby enhancing the photoelectric conversion efficiency of solar cells.
Smart Images

Figure CN116847706B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to perovskite thin films, and more particularly to a tin-based perovskite thin film, its preparation method, and its application. Background Technology
[0002] Over the past few decades, environmental pollution has become increasingly severe due to the overexploitation and use of fossil fuels. Solar cells, as a new clean energy source, have enormous potential to alleviate this problem. Perovskite solar cells, with their excellent photoelectric properties, long carrier diffusion distance, high light absorption coefficient, tunable bandgap, low exciton binding energy, and high defect tolerance, have made significant progress in the past decade.
[0003] Perovskite solar cells are a type of organic-inorganic halide hybrid perovskite thin-film solar cell with three functional layers: an electron transport layer (ETL), a hole transport layer (HTL), and a perovskite layer. Tin-based perovskite, compared to lead-based perovskite, has a more suitable bandgap, making it a preferred choice for fabricating high-efficiency solar cells. Furthermore, it is non-toxic, which facilitates commercialization. However, tin-based perovskite crystallizes faster than lead-based perovskite, which can lead to incomplete film coverage. Additionally, the perovskite crystallizes in island-like patterns on the substrate, resulting in significant leakage current and direct contact between the electron transport layer and the hole transport layer, ultimately causing device failure. Summary of the Invention
[0004] Based on the above analysis, one embodiment of the present invention aims to provide a tin-based perovskite thin film to solve the problems of poor stability and low coverage of tin-based perovskite thin films.
[0005] In a first aspect, one embodiment of the present invention provides a tin-based perovskite thin film comprising a chemical composition of RA. n- 1B n X 3n+1 The perovskite structure; where R represents a divalent terephthalic anion, A represents a monovalent organic cation, B represents a divalent tin ion, and X represents a halide ion.
[0006] According to one embodiment of the present invention, A represents formamidinium ion or methylamine ion.
[0007] According to one embodiment of the present invention, X represents an iodide ion.
[0008] According to one embodiment of the present invention, the value of n is 1 to 20.
[0009] According to one embodiment of the present invention, the value of n is 1 to 10.
[0010] According to one embodiment of the present invention, the value of n is 1, 4, 7 or 10.
[0011] According to one embodiment of the present invention, the value of n is 10.
[0012] Secondly, an embodiment of the present invention provides a method for preparing the above-mentioned tin-based perovskite thin film, comprising:
[0013] The first film layer was prepared by spin coating of a perovskite precursor solution; and
[0014] The first film layer is annealed to obtain the tin-based perovskite thin film.
[0015] The perovskite precursor solution includes terephthalic acid diammonium salt, organic ammonium salt, and tin salt.
[0016] According to one embodiment of the present invention, the terephthalic acid salt includes terephthalic acid hydroiodate, the organic ammonium salt includes formamidinium salt and / or methylamine salt, and the tin salt includes stannous fluoride and stannous iodide.
[0017] According to one embodiment of the present invention, the concentration of the perovskite precursor solution is 0.12 to 0.2 mol / L.
[0018] According to one embodiment of the present invention, the solvent of the perovskite precursor solution includes dimethyl sulfoxide and / or N,N-dimethylformamide.
[0019] According to one embodiment of the present invention, the annealing temperature is 70–100°C.
[0020] According to one embodiment of the present invention, the annealing process takes 10 to 30 minutes.
[0021] Thirdly, one embodiment of the present invention provides a solar cell comprising the aforementioned tin-based perovskite thin film.
[0022] According to one embodiment of the present invention, the solar cell includes:
[0023] Hole transport layer;
[0024] An absorption layer is disposed on the hole transport layer; and
[0025] An electron transport layer is disposed on the tin-based perovskite thin film;
[0026] The absorber layer includes the tin-based perovskite film.
[0027] Fourthly, one embodiment of the present invention provides a tandem solar cell comprising the aforementioned tin-based perovskite thin film.
[0028] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0029] 1. The tin-based perovskite thin film of one embodiment of the present invention has higher stability and higher substrate coverage compared with existing tin-based perovskite thin films.
[0030] 2. The solar cell of one embodiment of the present invention has a higher photoelectric conversion efficiency compared with existing tin-based perovskite solar cells.
[0031] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0032] The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of the invention. Wherein:
[0033] Figure 1 The XRD patterns are of the tin-based perovskite films prepared in Example 1 (S1) and Comparative Example 1 (D1) of the present invention.
[0034] Figure 2A This is a SEM image of the tin-based perovskite thin film of Comparative Example 1 of the present invention.
[0035] Figure 2B This is a SEM image of the tin-based perovskite thin film of Example 1 of the present invention;
[0036] Figure 3A This is a UV-Vis absorption diagram of the tin-based perovskite thin film of Example 1 of the present invention under air conditions at different times;
[0037] Figure 3B The UV-Vis absorption diagrams of the tin-based perovskite thin film of Comparative Example 1 of the present invention at different times under air conditions are shown.
[0038] Figure 4A The images show the XRD patterns of the tin-based perovskite films of Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M) of the present invention.
[0039] Figure 4B The photoluminescence spectra (PL) of the tin-based perovskite thin films of Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M) of the present invention are shown.
[0040] Figure 5AThe UV-Vis absorption spectra of the tin-based perovskite films of Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M) of the present invention are shown.
[0041] Figure 5B The band gap diagrams are for the tin-based perovskite films of Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M) of the present invention.
[0042] Figure 6A The image shows the UV-Vis absorption of the tin-based perovskite thin film of Example 2-1 of this invention at different times under air conditions.
[0043] Figure 6B The image shows the UV-Vis absorption of the tin-based perovskite thin film of Example 2-2 of this invention at different times under air conditions.
[0044] Figure 6C The images show the UV-Vis absorption of the tin-based perovskite thin films of Examples 2-3 of this invention at different times under air conditions.
[0045] Figure 7A The device efficiency JV diagrams for tin-based perovskite solar cells in Examples 3-1 (n=1), 3-2 (n=4), 3-3 (n=7), and 3-4 (n=10) of this invention are shown.
[0046] Figure 7B The figures show the device performance data of the tin-based perovskite solar cells in Examples 3-1 (n=1), 3-2 (n=4), 3-3 (n=7), and 3-4 (n=10) of this invention. Detailed Implementation
[0047] The preferred embodiments of the present invention will be described in detail below. The accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0048] One embodiment of the present invention provides a tin-based perovskite thin film comprising a chemical composition of RA. n-1 B n X 3n+1 The perovskite crystal structure; where R represents the divalent terephthalic anion (PDMA), A represents the monovalent organic cation, and B represents the divalent tin ion (Sn). 2+ ), where X represents a halide ion;
[0049] The structural formula of the terephthalic anion is as follows:
[0050]
[0051] The tin-based perovskite thin film of one embodiment of the present invention has PDMA organic cations inserted into the inorganic structure of perovskite (e.g., lead iodide octahedron) to form a network envelope structure, which prevents the migration of ions in the perovskite, inhibits its elemental diffusion, greatly increases the driving force of perovskite decomposition, and makes the perovskite structure more stable; moreover, the insertion of PDMA organic cations effectively improves the coverage of the film and slows down the crystallization rate of tin-based perovskite, which is beneficial to improving the performance of the obtained solar cell.
[0052] In one embodiment, A can be a formamidinium ion (FA) or a methylamine ion.
[0053] In one embodiment, X represents a halide ion, such as one or more of fluoride ions, chloride ions, bromide ions, and iodide ions; further, X represents an iodide ion.
[0054] In one embodiment, the value of n is 1 to 20, or more specifically 1 to 10. For example, the value of n can be 1, 2, 4, 7, or 10.
[0055] In one embodiment, the thickness of the tin-based perovskite film can be 300–500 nm, for example 350 nm, 400 nm, or 450 nm.
[0056] An embodiment of the present invention further provides a method for preparing the above-mentioned tin-based perovskite thin film, comprising:
[0057] The first film layer was prepared by spin coating of a perovskite precursor solution; and
[0058] The first film layer was annealed to obtain a tin-based perovskite thin film with a two-dimensional crystal structure.
[0059] The perovskite precursor solution includes terephthalic acid diammonium salt, organic ammonium salt, and tin salt.
[0060] In one embodiment, the perovskite precursor solution can be placed on a substrate for spin coating. The present invention does not have any particular limitation on the substrate, and an appropriate substrate can be selected according to the specific application. For example, the substrate can be a polythiophene derivative, polyethylene dioxythiophene (PEDOT).
[0061] In one embodiment, the substrate may be ozone treated prior to spin coating.
[0062] In one embodiment, the terephthalic acid salt can be terephthalic acid hydroiodate (hereinafter also referred to as PDMAI), the structure of which is shown below:
[0063]
[0064] In one embodiment, the organic ammonium salt may be a formamidinium salt and / or a methylamine salt, and may further be formamidinium hydroiodide (FAI).
[0065] In one embodiment, the tin salt includes stannous fluoride (SnF2) and stannous iodide (SnI2).
[0066] In one embodiment, the perovskite precursor solution can be prepared according to the n-value of the prepared perovskite structure, and the concentration of each component can be selected. The total concentration of the perovskite precursor solution can be 0.12–0.2 mol / L, for example, 0.12 mol / L, 0.15 mol / L, or 0.18 mol / L; SnF2 is used to suppress the oxidation of stannous iodide during the preparation process, and the molar ratio of SnF2 to SnI2 can be 1:10.
[0067] This invention does not limit the solvent of the perovskite precursor solution; the type of solvent can be selected according to the solubility of the precursor components. For example, the solvent of the perovskite precursor solution can be dimethyl sulfoxide (DMSO) and / or N,N-dimethylformamide (DMF), or more specifically, a mixed solvent of DMSO and DMF, with a volume ratio of DMSO:DMF = 4:1.
[0068] In one embodiment, the method for preparing the perovskite precursor solution includes: adding PDMAI, FAI, SnI2, and SnF2 to a mixed solvent of DMSO and DMF, and stirring at room temperature for 8 hours in a nitrogen oven to obtain the perovskite precursor solution.
[0069] In one embodiment, the volume of the perovskite precursor solution for spin coating can be 50–100 μL, for example, 60 μL, 70 μL, 80 μL, or 90 μL.
[0070] In one embodiment, the spin coating process for spin coating the perovskite precursor solution includes spin coating at a speed of 1000 rpm for 10 seconds, followed by spin coating at a speed of 5000 rpm for 25 seconds.
[0071] In one embodiment, the annealing temperature for the first film layer can be 70 to 100°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C; the annealing time can be 10 to 30 minutes, for example, 12 minutes, 15 minutes, 20 minutes, 25 minutes, 28 minutes, or 30 minutes.
[0072] The tin-based perovskite thin film of one embodiment of the present invention can be used in solar cells, for example, as an absorber layer in a solar cell.
[0073] One embodiment of the present invention provides a solar cell comprising the above-described tin-based perovskite thin film.
[0074] A solar cell according to one embodiment of the present invention includes:
[0075] Hole transport layer;
[0076] An absorption layer is disposed on the hole transport layer; and
[0077] An electron transport layer is disposed on the absorption layer;
[0078] The absorber layer includes the aforementioned tin-based perovskite thin film.
[0079] In one embodiment, the solar cell further includes a barrier layer disposed on the electron transport layer.
[0080] The tin-based perovskite thin film of one embodiment of the present invention can be used in tandem solar cells, especially all-perovskite tandem solar cells.
[0081] The tin-based perovskite thin film of one embodiment of the present invention can improve the stability of the fabricated solar cell by inserting p-phenylenediamine salt into the perovskite structure. In addition, compared with inserting a compound containing only one cation into the perovskite structure, the tin-based perovskite thin film of the present invention has better charge transport capability and more orderly interlayer distribution, which is beneficial to improving device performance and stability.
[0082] The preparation of a tin-based perovskite thin film and solar cell according to an embodiment of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Unless otherwise specified, all raw materials used are commercially available.
[0083] Example 1: Preparation of Tin-based Perovskite Thin Films
[0084] (1) PDMAI, FAI, SnI2, and SnF2 were added to a mixed solvent of DMSO and DMF (DMSO:DMF = 4:1), and stirred at room temperature in a nitrogen oven for 8 hours to obtain a perovskite precursor solution; wherein, the proportions of PDMAI, FAI, SnI2, and SnF2 were as specified in RA. n-1 B n X 3n+1 The composition was prepared with n=10, and the total concentration of the precursor solution was 0.12 mol / L (0.12 M), the concentration of PDMAI was 0.12 M, the concentration of FAI was 1.1 M, the concentration of SnI2 was 1.2 M, and the concentration of SnF2 was 0.12 M.
[0085] (2) Ozone treatment of the substrate, take 80ul of the precursor solution prepared in step (1) and drop it onto the substrate, spin coat at 1000rps for 10s, then spin coat at 5000rps for 25s to form the first film layer on the substrate, and obtain the “substrate / first film layer” structure.
[0086] (3) The “substrate / first film layer” structure was annealed at 100°C for 30 minutes to obtain a two-dimensional tin-based perovskite thin film.
[0087] Example 2-1 Preparation of Tin-based Perovskite Thin Films
[0088] This embodiment uses the same method and raw materials as in Example 1 to prepare tin-based perovskite thin films.
[0089] Example 2-2 Preparation of Tin-based Perovskite Thin Films
[0090] This embodiment uses the same method and raw materials as Example 2-1 to prepare tin-based perovskite thin films. The only difference is that the total concentration of the precursor solution in step (1) of Example 2-1 is 0.12 mol / L (0.12 M), while the total concentration of the precursor solution in step (1) of Example 2-2 is 0.16 mol / L (0.16 M).
[0091] Example 2-3 Preparation of tin-based perovskite thin films
[0092] This embodiment uses the same method and raw materials as Example 2-1 to prepare tin-based perovskite thin films. The only difference is that the total concentration of the precursor solution in step (1) of Example 2-1 is 0.12 mol / L (0.12 M), while the total concentration of the precursor solution in step (1) of Example 2-3 is 0.2 mol / L (0.2 M).
[0093] Comparative Example 1: Preparation of Tin-based Perovskite Thin Films (FASnI3)
[0094] (1) Use a nano sponge to apply detergent to clean the FTO side and glass side of the fluorine-doped tin dioxide (FTO) conductive glass substrate for 10 minutes each. Then place the substrate in a support and sonicate it in a beaker containing acetone for 30 minutes and in a beaker containing ethanol for 30 minutes.
[0095] (2) Remove the substrate, blow the surface of alcohol with a nitrogen gun, and treat with ozone for 15 minutes.
[0096] (3) FAI, SnI2, and SnF2 were added to a mixed solvent of DMSO and DMF (DMSO:DMF = 4:1), and stirred at room temperature in a nitrogen oven for 8 hours to obtain a precursor solution of FASnI3. The proportions of FAI, SnI2, and SnF2 were prepared according to the composition of FASnI3. The total concentration of the precursor solution was 1.2 mol / L (1.2 M), the concentration of FAI was 1.2 M, the concentration of SnI2 was 1.2 M, and the concentration of SnF2 was 0.12 M.
[0097] (4) Ozone treatment of the substrate, drop 80ul of the precursor solution prepared in step (3) onto the substrate, spin coat at 1000rps for 10s, then spin coat at 5000rps for 25s to form the first film layer on the substrate, and obtain the “substrate / first film layer” structure.
[0098] (5) The “substrate / first film layer” structure was annealed at 100°C for 30 minutes to obtain a three-dimensional tin-based perovskite thin film.
[0099] Example 3-1 Fabrication of Tin-based Perovskite Solar Cells
[0100] S1: Fabrication of the hole transport layer
[0101] (1) Use a nano sponge to apply detergent to clean the FTO side and glass side of the substrate for 10 minutes each. Then place the substrate in a support and sonicate it in a beaker containing acetone for 30 minutes and in a beaker containing ethanol for 30 minutes.
[0102] (2) Remove the substrate, blow the surface of alcohol with a nitrogen gun, and treat with ozone for 15 minutes;
[0103] (3) Place the ozone-treated substrate on a spin coater for PEDOT spin coating at a speed of 3000 rpm / s for 30 s with an acceleration of 3000 rpm / s. 2 The resulting structure was then placed on a hot plate for annealing at 150°C for 30 minutes to obtain the "substrate / hole transport layer" structure.
[0104] S2: Preparation of the absorption layer
[0105] Tin-based perovskite thin films were prepared using the same method and raw materials as in Example 1, with the only difference being that in step (1) of Example 1, the precursor solution was prepared at a ratio of n=10, while in this example, the precursor solution was prepared at a ratio of n=1. After the tin-based perovskite thin film was prepared, a "substrate / hole transport layer / absorption layer" structure was obtained.
[0106] S3: Fabrication of the electron transport layer
[0107] The "substrate / hole transport layer / absorbent layer" structure prepared above was placed on a spin coater, and a solution of [6,6]-phenyl C61 butyrate methyl ester (PCBM) was added to the surface of the absorbent layer. The spin coater speed was adjusted to 3000 rpm / s, the spin coat time to 30 s, and the acceleration to 3000 rpm / s. 2 Spin coating is performed; the spin-coated structure is annealed at 100℃ for 10 min to obtain the "substrate / hole transport layer / absorption layer / electron transport layer" structure.
[0108] S4: Preparation of the barrier layer
[0109] The "substrate / hole transport layer / absorber layer / electron transport layer" structure prepared above was placed on a spin coater. A solution of 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP) was added to the surface of the electron transport layer. The spin coater speed was adjusted to 6000 rpm / s, the spin coat time to 30 s, and the acceleration to 6000 rpm / s. 2 Spin coating is performed; the spin-coated structure is annealed at 100℃ for 1 min to obtain the "substrate / hole transport layer / absorber layer / electron transport layer / blocking layer" structure.
[0110] S5: Electrode Preparation
[0111] The structure obtained in step S4 is placed in a photomask, then into a vapor deposition apparatus, and finally the silver deposition material is added. The mechanical pump is turned on, and the pressure is allowed to reach 10... -1 At Pa, the molecular pump is turned on to continue evacuating to 10 Pa. -4 Pa, turn on the evaporation power supply, adjust the silver evaporation current to about 110A, control the evaporation rate to about 2 angstroms / s, and the evaporation thickness to 120nm. After the evaporation is completed, a tin-based perovskite solar cell is obtained.
[0112] Example 3-2 Fabrication of Tin-based Perovskite Solar Cells
[0113] This embodiment uses the same method and raw materials as Example 3-1 to prepare tin-based perovskite thin-film solar cells. The only difference is that in step S1(1) of Example 3-1, the precursor solution is prepared according to a ratio of n=1, while in this embodiment, the precursor solution is prepared according to a ratio of n=4.
[0114] Example 3-3 Fabrication of Tin-based Perovskite Solar Cells
[0115] This embodiment uses the same method and raw materials as Example 3-1 to prepare tin-based perovskite thin-film solar cells. The only difference is that in step S1(1) of Example 3-1, the precursor solution is prepared according to a ratio of n=1, while in this embodiment, the precursor solution is prepared according to a ratio of n=7.
[0116] Examples 3-4: Fabrication of Tin-based Perovskite Solar Cells
[0117] This embodiment uses the same method and raw materials as Example 3-1 to prepare tin-based perovskite thin-film solar cells. The only difference is that in step S1(1) of Example 3-1, the precursor solution is prepared according to a ratio of n=1, while in this embodiment, the precursor solution is prepared according to a ratio of n=10.
[0118] Comparative Example 2: Tin-based perovskite (BA2FA9Sn) 10 I 31Preparation of solar cells
[0119] S1: Fabrication of the hole transport layer
[0120] The hole transport layer was prepared using the same method and raw materials as in Example 3-1 to obtain a "substrate / hole transport layer" structure.
[0121] S2: Absorbing layer (BA2FA9Sn) 10 I 31 Preparation of thin films
[0122] (1) Butylamine hydroiodide (BAI), FAI, SnI2, and SnF2 were added to a mixed solvent of DMSO and DMF (DMSO:DMF = 4:1), and stirred at room temperature in a nitrogen oven for 8 hours to obtain a FASnI3 precursor solution; wherein, the proportions of BAI, FAI, SnI2, and SnF2 were as follows: BA2FA9Sn 10 I 31 The precursor solution was prepared with the following composition: total concentration of 0.12 mol / L, BAI concentration of 0.24 M, FAI concentration of 1.1 M, SnI2 concentration of 1.2 M, and SnF2 concentration of 0.12 M.
[0123] (2) Ozone treatment of the substrate, take 80ul of the precursor solution prepared in step (1) and drop it onto the substrate, spin coat at 1000rps for 10s, then spin coat at 5000rps for 25s to form the first film layer on the substrate, and obtain the "substrate / hole transport layer / first film layer" structure.
[0124] (3) The “substrate / hole transport layer / first membrane layer” structure was annealed at 100°C for 30 minutes to obtain the “substrate / hole transport layer / absorption layer”.
[0125] S2~S5: Fabrication of electron transport layer, blocking layer, and electrodes
[0126] Using the same methods and raw materials as in S2 to S5 of Example 3-1, an electron transport layer, a barrier layer, and electrodes were prepared to obtain a solar cell.
[0127] Comparative Example 3: Tin-based perovskite (PEA2FA9Sn) 10 I 31 Preparation of solar cells
[0128] This example uses the same method and raw materials as Comparative Example 2 to prepare a solar cell, the only difference being that (1) in the preparation of the S2 absorber layer is different from that in Comparative Example 2. S2(1) in this example includes:
[0129] PEAI, FAI, SnI2, and SnF2 were added to a mixed solvent of DMSO and DMF (DMSO:DMF = 4:1), and stirred at room temperature in a nitrogen oven for 8 hours to obtain a FASnI3 precursor solution; wherein the proportions of PEAI, FAI, SnI2, and SnF2 were as follows: PEA2FA9Sn 10 I 31 The precursor solution was prepared with the following composition: total concentration of 0.12 mol / L, concentration of PEAI of 0.24 M, concentration of FAI of 1.1 M, concentration of SnI2 of 1.2 M, and concentration of SnF2 of 0.12 M.
[0130] Among them, the chemical formula is PEA2FA9Sn 10 I 31 In this context, PEA represents the organic ammonium cation in PEAI. The structural formula of PEAI is as follows:
[0131]
[0132] The tin-based perovskite thin films and solar cells prepared in Examples 1 to 3-4 and Comparative Examples 1 to 3 were subjected to relevant performance tests. For specific results, please refer to [link to relevant documentation]. Figures 1 to 7B .
[0133] Figure 1 The images show the XRD patterns of the tin-based perovskite films prepared in Example 1 (S1) and Comparative Example 1 (D1). As described in Example 1 and Comparative Example 1, the film of Comparative Example 1 lacks the insertion of PDMAI compared to the film of Example 1. Figure 1 A comparison of the S1 and D1 spectra in Example 1 shows that, due to the insertion of the large cation PDMA, the inorganic interlayer spacing of the perovskite lead iodide octahedron in Example 1 is expanded. According to Bragg's law, the S1 spectrum shows small-angle diffraction peaks, indicating the formation of a two-dimensional structure.
[0134] Figure 2A , 2B SEM images of the tin-based perovskite films of Comparative Example 1 and Example 1 are shown below. Figure 2A As shown, in the tin-based perovskite film of Comparative Example 1, the perovskite structure is distributed in a small island-like pattern on the substrate. This indicates poor film density, preventing high-density coverage of the substrate and leaving many areas exposed. If this type of film is applied to a solar cell, the low coverage will cause direct contact between the electron transport layer and hole transport layer on both sides of the film, leading to severe leakage and ultimately device failure. The main reasons why the tin-based perovskite film of Comparative Example 1 cannot achieve high-density substrate coverage are twofold: firstly, the crystallization rate of tin-based perovskite is too fast, making it difficult to form high-quality large grains; secondly, its extremely low stability makes the film susceptible to degradation by water and oxygen.
[0135] In Embodiment 1 of this invention, by adding organic cationic PDMA to the tin-based perovskite precursor, the crystallization rate of the tin-based perovskite can be effectively slowed down, resulting in more compact and coherent grain growth and improved crystal quality of the perovskite film. Furthermore, by inhibiting the water-oxygen interaction channels, the perovskite film is protected from degradation, ultimately yielding a perovskite film with high coverage. The specific structure is as follows: Figure 2B As shown.
[0136] Figure 3A , 3B The images show the UV-Vis absorption spectra of the tin-based perovskite films from Example 1 and Comparative Example 1 at different times under air conditions. Figure 3A It can be seen that the UV-Vis absorption spectrum of the tin-based perovskite thin film of Example 1 of the present invention did not change significantly within 2 hours, indicating that it has high stability. And as... Figure 3B As shown, the UV-Vis absorption of the tin-based perovskite film in Comparative Example 1 decreased significantly after two hours. These results clearly demonstrate that the tin-based perovskite film of Example 1 of this invention has higher stability than the tin-based perovskite film of Comparative Example 1, further indicating that adding PDMA organic cations to the tin-based perovskite film can significantly improve its stability.
[0137] Figure 4A , 4B The images show the XRD patterns and photoluminescence spectra of the tin-based perovskite films from Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M), respectively. Figure 4A It can be seen that small-angle diffraction peaks representing two-dimensional structures appeared in the XRD patterns of tin-based perovskite films prepared with perovskite precursor solutions of different concentrations, indicating the presence of two-dimensional structures in the perovskite films; simultaneously, through... Figure 4A It can be seen that among the three thin films, the 0.12M film exhibits the strongest diffraction peak at 14°, indicating its best crystallinity. Therefore, the preferred total concentration of the perovskite precursor solution used for film preparation is 0.12 mol / L. See further... Figure 4B It can be seen that there is a short-wavelength exciton peak in PL, and the appearance of this peak also indicates the existence of a two-dimensional structure.
[0138] Figure 5A , 5B The UV-Vis absorption spectra and band gap diagrams of the tin-based perovskite films from Examples 2-1 (0.12M), 2-2 (0.16M), and 2-3 (0.2M) are shown. Figure 5A It can be seen that the UV-Vis absorption spectrum shows a significant uplift at 700 nm, indicating the presence of a two-dimensional structure in the thin film; in addition, the corresponding Figure 4BSmall-angle exciton peaks can also be seen in the photoluminescence spectrum. According to... Figure 5B As shown, as the concentration of the perovskite precursor solution decreases, the band gap of the resulting film decreases, which is beneficial to the increase of current density.
[0139] Figures 6A to 6C The figures show the UV-Vis absorption spectra of the tin-based perovskite films of Examples 2-1 to 2-3 under air conditions over time. As can be seen from the figures, the absorbance of the tin-based perovskite films did not decrease with increasing time. Figures 6A to 6C The curve is normalized. The absorbance increases slightly after 0.5h, 1h, and 2h. This may be due to the displacement of the perovskite film on the sample stage. The fluctuation is less than 0.1, which is within a reasonable fluctuation range.
[0140] Figure 7A , 7B The figures show the device efficiency (JV) and performance data of tin-based perovskite solar cells for Examples 3-1 (n=1), 3-2 (n=4), 3-3 (n=7), and 3-4 (n=10), respectively. Due to the unique symmetric structure of PDMA, when the value of n is small, the PDMA spacer exists between the inorganic layers in a conventional manner, with the larger insulating organic layer and the conductive inorganic layer forming a quantum well structure with quantum confinement. When the value of n is large, the spatial existence state of the PDMA spacer between the inorganic layers changes, and in this state, the spacing between the inorganic layers becomes smaller, forming an unconfined structure. From... Figure 7A It can be seen that increasing the number of inorganic layers leads to a decrease in the open-circuit voltage and an increase in the short-circuit current density of tin-based perovskite solar cell devices. However, within a certain range, the change in the number of inorganic layers has little effect on device performance. Figure 7B It can be seen that the battery device with n=10 exhibits 16.27 mA / cm². 2 It has the highest current density and the highest photoelectric conversion efficiency of 2.7%.
[0141] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A tin-based perovskite thin film comprising a chemical composition of RA n-1 B n X 3n+1 The perovskite crystal structure; among which, R represents a divalent terephthalic anion, A represents a monovalent organic cation, B represents a divalent tin ion, and X represents a halide ion; the value of n is 1 to 20.
2. The tin-based perovskite thin film according to claim 1, wherein, A represents formamidinium ion or methylamine ion; and / or, X represents iodide ions.
3. The tin-based perovskite thin film according to claim 1, wherein, The value of n is 1 to 10.
4. The tin-based perovskite thin film according to claim 1, wherein, The value of n is 1, 4, 7 or 10.
5. A method for preparing a tin-based perovskite thin film according to any one of claims 1 to 4, comprising: The first film layer was prepared by spin coating of the perovskite precursor solution. as well as The first film layer is annealed to obtain the tin-based perovskite thin film. The perovskite precursor solution includes terephthalic acid diammonium salt, organic ammonium salt, and tin salt. The terephthalic acid salt includes terephthalic acid hydroiodate, the organic ammonium salt includes formamidinium salt or methylamine salt, and the tin salt includes stannous fluoride and stannous iodide.
6. The method according to claim 5, wherein, The concentration of the perovskite precursor solution is 0.12–0.2 mol / L.
7. The method according to claim 5, wherein, The solvent for the perovskite precursor solution includes dimethyl sulfoxide and / or N,N-dimethylformamide.
8. The method according to claim 5, wherein, The annealing process is performed at a temperature of 70–100°C for 10–30 minutes.
9. A solar cell comprising a tin-based perovskite thin film according to any one of claims 1 to 4, or a tin-based perovskite thin film prepared by the method according to any one of claims 5 to 8.
10. A tandem solar cell comprising a tin-based perovskite thin film according to any one of claims 1 to 4, or a tin-based perovskite thin film prepared by any one of claims 5 to 8.
Citation Information
Patent Citations
Phase-pure, two-dimensional, multilayered perovskites for optoelectronic applications
US20180301646A1
